Psychosis and aggression in Alzheimer's disease: the effect of dopamine receptor gene variation. Issue 6 (1st December 2001) - Holmes, C; Smith, H; Ganderton, R; Arranz, M; Collier, D; Powell, J; Lovestone, S
Abstract : This study investigated possible associations between selected polymorphisms in the dopamine receptor genes DRD1 and DRD3 with the presence of psychotic phenomena or aggressive behaviour in a community based cohort of 134 patients with late onset Alzheimer's disease. An association was found between the presence of psychotic symptoms and aggressive behaviour and the DRD1 polymorphism and between the presence of psychosis, but not aggression, and the DRD3 polymorphism. Specifically, carriers of the DRD1 B2 allele were more likely to be aggressive or experience hallucinations whereas homozygous carriers of the DRD3 1 allele were more likely to experience delusions.